Neurotransmitters Modulate Intrathymic T-cell Development - Francelin, Carolina; Veneziani, Luciana Peixoto; Farias, Alessandro dos Santos; Mendes-da-Cruz, Daniella Arêas; Savino, Wilson (Frontiers in Cell and Developmental Biology, 2021)
The existence of a crosstalk between the nervous and immune systems is well established. Neurotransmitters can be produced by immune cells, whereas cytokines can be secreted by cells of nervous tissues. Additionally, cells of both systems express the corresponding receptors. Herein, we discuss the thymus as a paradigm for studies on the neuroimmune network. The thymus is a primary lymphoid organ responsible for the maturation of T lymphocytes. Intrathymic T-cell development is mostly controlled by the thymic microenvironment, formed by thymic epithelial cells (TEC), dendritic cells, macrophages, and fibroblasts. Developing thymocytes and microenvironmental cells can be influenced by exogenous and endogenous stimuli; neurotransmitters are among the endogenous molecules. Norepinephrine is secreted at nerve endings in the thymus, but are also produced by thymic cells, being involved in controlling thymocyte death. Thymocytes and TEC express acetylcholine receptors, but the cognate neurotransmitter seems to be produced and released by lymphoid and microenvironmental cells, not by nerve endings. Evidence indicates that, among others, TECs also produce serotonin and dopamine, as well as somatostatin, substance P, vasoactive intestinal peptide and the typical pituitary neurohormones, oxytocin and arg-vasopressin. Although functional data of these molecules in the thymus are scarce, they are likely involved in intrathymic T cell development, as exemplified by somatostatin, which inhibits thymocyte proliferation, differentiation, migration and cytokine production. Overall, intrathymic neuroimmune interactions include various neurotransmitters, most of them of non-neuronal origin, and that should be placed as further physiological players in the general process of T-cell development.